2015
DOI: 10.1017/s1479262115000374
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of maize diversity in Yucatan, Mexico: influence of agro-ecological factors on landraces conservation and modern variety introduction

Abstract: Transformations that farmers bring to their traditional farming systems and their impacts on the conservation and evolution of maize varieties over a 12-year period are investigated using a longitudinal analysis. Despite the increased introduction and supply of improved maize variety seeds in the Yucatan Peninsula, Mexico, over the last 12 years farmers continue to maintain a substantial amount of traditional maize variety diversity. Even with the increased availability of hybrid seeds, farmers in the communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
1
25
0
3
Order By: Relevance
“…Our longitudinal study allowed us to examine in situ conservation from a novel perspective (Ortega-Paczka 1973;Fenzi et al 2015). For the first time, we interviewed the same group of farmers' families after a 50-year period and systematically collected evidence on how farmers were affected by multiple factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our longitudinal study allowed us to examine in situ conservation from a novel perspective (Ortega-Paczka 1973;Fenzi et al 2015). For the first time, we interviewed the same group of farmers' families after a 50-year period and systematically collected evidence on how farmers were affected by multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…For maize in Mexico, the factors associated with in situ conservation have been extensively researched. Documented evidence linked conservation to farmers' management of heterogeneous environments, soils, pests, pathogens and climate risk (Ortega-Paczka 1973;Bellon 1991Bellon , 1996Bellon and Taylor 1993;Bellon and Brush 1994;Fenzi et al 2015), farmers' ethnicity (Brush and Perales 2007), use and consumption preferences (Perales et al 2003a;Bellon and Hellin 2011), and farm scale ). These findings have been used to design conservation interventions (Bellon 2004) and to identify the most promising areas for their costeffective implementation (Smale et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gene coding regions are comprised of full transporter (FT) versions that have paired nucleotide binding domain (NBD) and transmembrane domain (TMD) or a half transporter (HT) that have one each of the NDB and TMD, and hetero- or homodimerization of the latter is required for functionality 122 . Fifty one ABC transporter protein coding regions were identified in the B. mori genome and classified into within 8 subgroups by phylogenetic analysis (A-H) 123 . Bt resistance mechanisms have implicated a number of ABC transporters from subgroups A 124 , C 34 - 36 , 46 and G 39 (see Introduction for additional details), and interestingly members from these three subgroups were down-regulated in Cry1Ab and Cry1Ac resistant O. furnacalis ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…While we seek to take advantage of the locally available diversity for developing a robust hybrid breeding programme, the fear of genetic erosion with the introduction of hybrids also needs to be addressed. Studies have shown that despite introduction of hybrids, cultivation of traditional landraces continues to thrive in areas of crop diversity since it is community based, depends on an informal seed exchange system and is strongly dictated by cultural preferences of the indigenous people involved (Bellon and Hellin, 2011; Fenzi et al ., 2015). Also, at the individual level, depending on the farmers' perception there is always a tradeoff between utilization of genetic resources (local/improved varieties) available at his/her disposal.…”
Section: Discussionmentioning
confidence: 99%